E-voting system project in Laravel based on web-based application / Anis Natasha Zahimi and Ros Syamsul Hamid - Zahimi, Anis Natasha; Hamid, Ros Syamsul (College of Computing, Informatics and Media, UiTM Perlis, 2023)
As part of this course requirement, the project will discuss the planning and execution of an online voting system. Voters are provided with a dependable and highly secure environment to cast their ballots through the use of internet terminals, which are personal computers, through the online voting system. In this voting method, the voter is not required to physically travel to the polling place in order to cast their vote. They are able to vote using their own personal computers immediately which can save a lot of time. There is a database that is kept up to date, and it saves all of the information pertaining to the users, including the full extent of that information. Simply filling out a registration form is all that is required for the System Administrator to register voters as they are eligible to vote. After they have registered, they will be able to vote for a certain party and candidate. The counting procedure is totally automated, therefore there is no opportunity for error or possibility for the results to be manipulated. When the analysis has been completed, the results, together with any accompanying statistical studies and graphical representations, will be published on the results page.